2009
DOI: 10.1111/j.1469-8137.2009.02870.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene contributes to potato aphid susceptibility in a compatible tomato host

Abstract: Summary• Resistance to potato aphid (Macrosiphum euphorbiae) in tomato (Solanum lycopersicum) is conferred by Mi-1. Early during both compatible and incompatible interactions, potato aphid feeding induces the expression of ethylene (ET) biosynthetic genes. Here, we used genetic and pharmacologic approaches to investigate the role of ET signaling in basal defense and Mi-1-mediated resistance to potato aphid in tomato.• The effect of potato aphid infestation on ET biosynthesis in susceptible and resistant plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 72 publications
(94 reference statements)
1
56
0
1
Order By: Relevance
“…Alterations in ET also benefit aphids, increasing insect fecundity on infected plants and therefore the number of viruliferous aphids. Virus infection and aphid feeding have been shown to influence the production of ET (Love et al, 2005(Love et al, , 2007Kim et al, 2008;Mantelin et al, 2009;Chen et al, 2013;Haikonen et al, 2013;Mandadi et al, 2014;Mauck et al, 2014), though ET's role in vector-virusplant interactions has not yet been demonstrated. Virus-induced changes in ET responses may mediate vector-plant interactions more broadly and thus represent a conserved mechanism for increasing transmission by insect vectors across generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in ET also benefit aphids, increasing insect fecundity on infected plants and therefore the number of viruliferous aphids. Virus infection and aphid feeding have been shown to influence the production of ET (Love et al, 2005(Love et al, , 2007Kim et al, 2008;Mantelin et al, 2009;Chen et al, 2013;Haikonen et al, 2013;Mandadi et al, 2014;Mauck et al, 2014), though ET's role in vector-virusplant interactions has not yet been demonstrated. Virus-induced changes in ET responses may mediate vector-plant interactions more broadly and thus represent a conserved mechanism for increasing transmission by insect vectors across generations.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in ET production following aphid feeding also have been reported in various plant-aphid interactions. However, ET production has been associated with both increased susceptibility and resistance to aphids (Miller et al, 1994;Argandoña et al, 2001;Mantelin et al, 2009;Lu et al, 2014;Wu et al, 2015). The role of ET in both plant-virus and plant-aphid interactions Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced population expansion was observed in green peach aphids (Myzus persicae) when raised on the Arabidopsis (Arabidopsis thaliana) constitutive expression of vegetative storage protein1 mutant constantly expressing JA responses, whereas the JA-insensitive mutant coronatine-insensitive1 supports more rapid growth of aphids than wild-type plants (Ellis et al, 2002;Mewis et al, 2005). Aphid infestation has been shown to trigger ET production (Mantelin et al, 2009). Elevated ET levels have been both positively and negatively correlated with plant resistance to aphids (Thompson and Goggin, 2006).…”
mentioning
confidence: 99%
“…Elevated ET levels have been both positively and negatively correlated with plant resistance to aphids (Thompson and Goggin, 2006). In tomato (Solanum lycopersicum), ET biosynthesis renders plants more susceptible to potato aphids (Macrosiphum euphorbiae; Mantelin et al, 2009). However, the Arabidopsis ET-insensitive mutant ein2 promotes performance of green peach aphids (Kettles et al, 2013), indicating that ET plays a defensive role in Arabidopsis.…”
mentioning
confidence: 99%
“…Therefore, other techniques are required to elucidate gene function. Virusinduced gene silencing (VIGS) offers an attractive alternative (Mitra et al, 2008;Pandey and Baldwin, 2008;Mantelin et al, 2009). Initially, VIGS was almost exclusively performed in the model plant species Nicotiana benthamiana by using vectors derived from tobacco mosaic virus (TMV) (Kumagai et al, 1995), potato virus X (Ratcliff et al, 1997), and tobacco rattle virus (TRV) (Ratcliff et al, 2001;Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%